Essential Oil of Lippia origanoides Kunth: Nanoformulation, Anticholinesterase Activity, and Molecular Docking - Antônio Quaresma da Silva Júnior; Gabriela dos Santos Rodrigues; Adenilson de Sousa Barroso; Pablo Luis Baia Figueiredo; Francisco Paiva Machado; Mikaela Amaral Ferreira; Caio Pinho Fernandes; Gabriela B. dos Santos; Rosa Helena V. Mourão (Molecules)
This study investigates the therapeutic potential of Lippia origanoides essential oil (LOEO) in neurological and pharmaceutical applications. The chemical composition of LOEO was analyzed using gas chromatography–mass spectrometry (GC-MS), revealing major constituents, such as carvacrol, thymol, and γ-gurjunene, known for their antioxidant and antimicrobial properties. LOEO demonstrated significant acetylcholinesterase (AChE)-inhibitory activity, particularly in a nanoformulation that enhances bioavailability and stability. Additionally, the major constituent carvacrol, when tested in isolation, also exhibited AChE-inhibitory activity comparable to that of the nanoformulation. Molecular docking analysis indicated strong binding affinities between LOEO compounds and AChE, supporting its therapeutic potential for neurodegenerative diseases like Alzheimer’s. Additionally, in silico pharmacokinetic predictions revealed favorable absorption and blood–brain barrier penetration profiles for key constituents. Despite promising results, this study acknowledges the need for in vivo validation and long-term stability assessments of the nanoformulation. Future research should focus on pharmacodynamic studies and evaluating the oil’s effectiveness in animal models. These findings highlight LOEO as a valuable candidate for developing natural therapies for neurodegenerative diseases.